2021
DOI: 10.22271/oral.2021.v7.i3c.1300
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in caries status of the first permanent molars in Libyan children

Abstract: To assess the prevalence and sex disparities for caries in the first permanent molars (FPMs) in Benghazi city, Libya. Methods: A cross-sectional study was conducted of 375 children (206 girls and 169 boys) of age 6-12 at pediatric clinic of Faculty of Dentistry. Data were analyzed using SPSS version 16, Chi square tests. Results: Caries prevalence in FPMs amongst all of the age groups 6-12 year-old was 675 teeth (45%). Contrary to national and international trends, there was no significant difference in caries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
1
2
1
Order By: Relevance
“…On the other hand, other studies were not in accordance with the finding of this study reported that girls had higher caries experience than boys [7,13,14,16,30,43,44]. Unfortunately, in Libya there is increasing levels of dental caries, the reason may be due to the lack of oral health care access among schoolchildren with an increase unmet treatment needs, lifestyle changes, easy access to unhealthy foods, dietary habits and higher consumption of sugared foods and drinks particularly among children, the preventive programs are not established and inadequate access to dental care.…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, other studies were not in accordance with the finding of this study reported that girls had higher caries experience than boys [7,13,14,16,30,43,44]. Unfortunately, in Libya there is increasing levels of dental caries, the reason may be due to the lack of oral health care access among schoolchildren with an increase unmet treatment needs, lifestyle changes, easy access to unhealthy foods, dietary habits and higher consumption of sugared foods and drinks particularly among children, the preventive programs are not established and inadequate access to dental care.…”
Section: Discussioncontrasting
confidence: 99%
“…12,17 These are in agreement with current study. Though improvement of the oral health and treatment of early childhood caries have not totally eliminated the risk of caries development in the first permanent molar.…”
supporting
confidence: 92%
“…Mohammad et al also have similar findings in the study conducted at Benghazi. 12 Second deciduous tooth was found to be carious in 17.6% children in this study and also had carious first permanent in these children. There was a significant difference in the children with early childhood caries and first permanent molar caries.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation